2014
DOI: 10.1159/000359950
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Peripheral Immune Challenge Activates Microglia and Inhibits Neurogenesis in the Developing Murine Hippocampus

Abstract: The early postnatal period represents an important window in rodent hippocampal development with peak hilar neurogenesis and widespread microgliogenesis occurring in the first week of life. Inflammation occurring during this period may negatively influence development, potentially facilitating or increasing susceptibility to later-life pathology. We administered the Gram-negative bacterial coat protein lipopolysaccharide (LPS) systemically at postnatal day 5 (1 mg/kg i.p.) and assessed potential effects on mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 49 publications
4
69
0
Order By: Relevance
“…25,26 Thus altered microbial communities could influence neurodevelopmental outcomes. Neurodevelopmental outcomes are of prime importance to neonatology.…”
Section: Microbiota-gut-brain Axismentioning
confidence: 99%
“…25,26 Thus altered microbial communities could influence neurodevelopmental outcomes. Neurodevelopmental outcomes are of prime importance to neonatology.…”
Section: Microbiota-gut-brain Axismentioning
confidence: 99%
“…Similarly, a higher dose of LPS (10 mg/kg s.c.) in P2 mice was associated with impaired oligodendrocyte maturation and reduced myelin production, without oligodendrocyte cell death or axonal injury, while a similar insult at P3, P4 or P5 had no obvious effects [88]. Nevertheless, a single dose of 1 mg/kg LPS in P5 rat pups was associated with persistent changes in microglial-phenotype-related genes, with a transient inhibition of the neuronal differentiation pathway for up to 2 weeks [89]. Consistent with persistent changes in response to inflammation, although neonatal LPS exposure at P5 did not lead to death of dopaminergic neurons in the substantia nigra, there were persistent functional alterations in the dopaminergic system and the substantia nigra at P70, as well as increased susceptibility to damage by very low-dose rotenone that was nontoxic in control animals [90].…”
Section: Postnatal Infection/inflammation In Rodentsmentioning
confidence: 99%
“…In neonate rodents, immune challenge has been reported to stimulate the production of proinflammatory cytokines, such as interleukin(IL)-1β, IL-6 and tumor necrosis alpha (TNFα), both at the periphery and in the brain [7], together with enhanced corticosterone levels [8]. These factors have been proposed to adversely impacts fetal brain development [9,10] such as hippocampal neurogenesis [11]. Studies in rodents have shown that postnatal day (PND)14 is a crucial period for brain network maturation.…”
Section: Introductionmentioning
confidence: 99%